Response of Macro Economy of Pakistan to External and Internal Shocks (Journal of Gender and Social Issues, 2022)
This study assesses external business cycle shocks to the economy of Pakistan using a Structural Vector Autoregressive (SVAR) framework consisting of five variables: gross domestic product, public investment, exchange rate, CPI, and openness of trade. The real exchange rate shock seems to be most volatile, and is responsible for significant movement in the rest of the variables in the system. The results indicate that terms of trade and exchange rate shocks have profound impacts on the system, and it can be generally concluded that external shocks have a strong bearing on the economy of Pakistan in both the short and long run. The study found that GDP is positively affected by public spending and terms of trade. Therefore, in general, we conclude that the economy of Pakistan is prone to be affected by external events.
Keywords: E32 Business Fluctuations; Cycle; F31 Foreign Exchange; H5 National Government Expenditures and Related Policies